Building a Smart City: Insights and Perspectives from the Winners of Smart City Challenge - Maloku, Andi (Scholarship@Western, 2019)
When Canadian Government launched smart city initiative over 130 municipalities, large and small have submitted their innovative ideas. On May 14, 2019, the four winners of the Canadian Smart Cities Challenge were announced in Ottawa: Town of Bridgewater, Nova Scotia winning $5M Prize Category; the Nunavut Communities, Nunavut winning $10M Prize Category; the City of Guelph and Wellington County, Ontario winning $10M Prize Category and the City of Montréal, Quebec winning $50M Prize Category. This paper focuses on these four cities by exploring two main research questions: (1) what does “smart cities” mean for Canadian municipalities; and, (2) what are the elements of smart city initiatives in Canada? This paper aims to build an understanding of smart city initiatives in Canadian context and explore what smart city means for Canadian municipalities. Based on previous research, the main areas explored in this research are categorized in eight aspects including (1) technology, (2) management and organization, (3) policy context, (4) governance, (5) people and communities, (6) economy, (7) built infrastructure and (8) natural environment.